Identifikasi kompetensi manajerial pada level manajemen menengah dalam industri perbankan Indonesia - Jeni Wulandari (Jurnal Siasat Bisnis, 2018)
The purpose if this study is to identify managerial competencies at middle management level in Indonesian banking industry. The study was conducted using a mixed method approach and the competeny menu and database a generic competency model of managersbySpencer & Spencer (1993). The results of the study propose a preliminary managerial competency model that demonstrates general competencies and key competencies for middle managers in banking industry that can be used as a framework in developing competency models in the Indonesian banking industry. This study presents perspectives and methods that provide further support and expansion in competency studies.